The impact of irritable bowel syndrome on daily functioning: Characterizing and understanding daily consequences of IBS. Issue 4 (25th October 2016) - Ballou, S.; Keefer, L.
Abstract: Background: Despite the well‐documented economic and psychosocial burden of irritable bowel syndrome (IBS), few studies have focused on the impact of IBS on daily activities. This study aims to quantitate impairment in daily activities among IBS patients and to evaluate the relationship between impairment, IBS, quality of life, and psychiatric symptoms. Methods: A total of 179 participants meeting ROME‐III criteria for IBS completed an online research survey evaluating the following variables: (i) the impact of IBS on daily activities, (ii) comorbid psychiatric diagnoses, (iii) symptom severity, (iv) quality of life, and (v) symptom‐specific cognitive affective factors related to IBS. Key Results: This sample reported a high degree of impairment due to IBS, with 76% of the sample reporting some degree of IBS‐related impairment in at least five different domains of daily life. Rates of impairment were significantly higher for participants who met criteria for anxiety, depression, and/or panic disorder. Conclusions & Inferences: This study contributes to existing literature by demonstrating a high level of daily impairment among patients with IBS, particularly those who meet criteria for anxiety, depression, and panic disorder. These findings support the importance of integrated psychosocial and medical care for IBS patients, and highlight the utility of evaluation and intervention for behavioral avoidance/impairment especially among those who exhibit signs or symptoms of psychiatric diagnoses. Abstract : This study characterizes daily impairment in patients with IBS. The majority of respondents reported impairment in at least five domains of daily living. Rates of impairment were highest among participants who met questionnaire‐based criteria for psychiatric diagnoses.